Oral manifestations in patients undergoing chemotherapy or radiotherapy treatment: A literary review (Research, Society and Development, 2024)
Introduction: Cancer is characterized by abnormal manifestations of cells that cause deterioration of body tissues. It is possible to observe that patients undergoing treatment have significant dental needs that require care prior to oncotherapy. Objective: To evaluate oral manifestations in cancer patients resulting from chemotherapy and radiotherapy treatments through a literature review. Methodology: This research is an integrative literary review. The scientific basis was carried out in the following databases: Virtual Health Library, Scientific Electronic Library Online and PubMed, using search terms such as Dentistry, Oncology, oral symptoms and chemotherapy treatment, covering the period from 2018 to 2023. Results: In agreement with the eligibility criteria, 125 articles were found, after screening the literature, 10 articles were included and had data tabulated. Conclusion: It is concluded that radiotherapy and chemotherapy treatment cause oral manifestations that negatively influence the quality of life of individuals.